A score of bioavailable strontium isotope archaeology in China: Retrospective and prospective - Tang, Zihua; Wang, Xueye (Frontiers in Earth Science, 2023)
Bioavailable strontium isotope analysis was proposed for prehistoric human ecology almost forty years ago and rapidly became one of the most important tools to trace past migratory behaviours. Since its first introduction to China in 2003, this method has greatly improved our understanding of migrations on individual- and community-scales over the past twenty years. This paper summarizes the current state of knowledge regarding identifying non-locals, utilizing animal resources, and strontium isoscapes for China based on empirical data. By incorporating additional baseline data, we updated and extended the current bioavailable strontium isoscape for China and Southeast and South Asia. These data will shed new light on intercultural communications and the spread of customs and technologies. In the future, strontium isotope analysis will involve an integrated provenancing system along with multiple approaches such as various isotopes and different modellings. Correspondingly, the existing isoscape needs to improve its spatial resolution and predictive accuracy to source the non-local archaeological biological remains. Furthermore, advances in analytical techniques allow us to reconstruct lifetime mobility of animals and humans at high temporal resolution.